Afiksasi dan Pengaruhnya terhadap Konstruksi Sintaksis Bahasa Jawa Kuna - Muhammad Badrul Anwar; Harum Munazharoh (Universitas Insan Budi Utomo, 2025)
This article departs from the use of language affixation to change syntactic constructions in sentence grammar. Prefixes in Old Javanese are